Advances and prospects of lasers developed from colloidal semiconductor nanostructures. (August 2018) - Wang, Yue; Sun, Handong
Abstract: Since the first observation of stimulated emission from colloidal quantum dots (CQDs) in year 2000, tremendous progress has been made in developing solution-processed lasers from colloidal semiconductor nanostructures in terms of both understanding the fundamental physics and improving the device performance. In this review paper, we will start with a brief introduction about the fabrication of CQDs and the corresponding electronic structures. The emphasis will be put on the discussion about the optical gain and lasing from colloidal nanostructures including the gain mechanism, the main hurdles against optical gain and lasing as well as strategies to optimize the lasing performance. Afterwards, the recent advances in CQD lasers, exemplified by the achievement of continuous wave lasing, will be presented. Finally, the challenges and a perspective of the future development of lasers based on the colloidal semiconductor nanostructures will be presented.